Neuroprotective evaluation of novel substituted 1, 3, 4-oxadiazole and aroylhydrazone derivatives. (1st March 2022) - Karabeliov, Valentin R.; Kondeva-Burdina, Magdalena S.; Vassilev, Nikolay G.; K.-Yovkova, Elena; Angelova, Violina T.
Graphical abstract: Highlights: Oxadiazole and hydrazone derivatives were designed and synthesized in good yield. The effects of the new derivatives on isolated rat brain synaptosomes were evaluated. The possible mechanisms of neuroprotection of the compounds might be a result from the inhibition of hMAOB, which catalyze the production of neurotoxic p-quinone from 6-OHDA. These compounds also showed high blood–brain barrier permeability. Abstract: The paper reports on the facile and convenient synthesis of a series of novel 2, 5-substituted 1, 3, 4-oxadiazoles 3a-f and that of aroylhydrazone-based molecular hybrids 5a-g from readily available starting materials. The structure of the compounds was confirmed by IR, 1 H NMR, 13 C NMR and HRESI-MS spectral data. The toxicological potential of the compounds was evaluated by monitoring the synaptosomal viability and the levels of reduced glutathione in rat brain synaptosomes, isolated by Percoll gradient. The neuroprotective effects were assessed in vitro in a model of 6-hydroxydopamine-induced neurotoxicity. Administered alone, at a concentration of 40 µM, most of the 1, 3, 4-oxadiazole derivatives and all of the hydrazone derivatives exhibited weak statistically significant neurotoxic effects, compared to the control. Two of the compounds from the novel oxadiazoles 3a and 3d did not have any toxicity. In a model of 6-OHDA-induced oxidative stress, again 3a and 3d and all aroylhydrazone derivatives 5a-g revealed statistically significant neuroprotective effect by preserving the synaptosomal viability and the level of reduced glutathione, against the toxic agent. Some of the compounds may have neuroprotective effects due to possible stabilization of the synaptosomal membrane and/or because of the preserved reduced glutathione. Additionally, all the compounds display a good predicted ADME profile.